Desire, Resentment and Reprisal: Revisiting the Emotions of Myth in F. Scott Fitzgerald’s The Great Gatsby - Gualberto Valverde, Rebeca (Amaltea. Revista de Mitocrítica, 2015)
This article aims to reassess F. Scott Fitzgerald’s classic The Great Gatsby (1925), taking into consideration the myth-critical hypotheses of philosopher René Girard. Specifically, this essay will analyse the concepts of mimetic desire, resentment and reprisal violence as emotional components of myth, paying close attention to how the reinterpreted mythical pattern of the novel influences the depiction of such emotions as social traits of corruption. Finally, this article will challenge interpretations that have regarded Gatsby as a successful scapegoat-figure, examining instead how the mythical meanings and structures of the text stage an emotional crisis of frustrated desire and antagonism that ultimately offers no hope of communal restoration.